1976
DOI: 10.1080/15287397609529444
|View full text |Cite
|
Sign up to set email alerts
|

Administration of aspartame in non‐insulin‐dependent diabetics

Abstract: A study was designed to determine the effect of the consumption of the nutritive sweetener aspartame on non-insulin-dependent diabetics. Forty-three adult diabetics between the ages of 21 and 70 completed a 90-day study; all were diabetics whose conditions were managed by diet and/or hypoglycemic agents. Participants in the blind study were instructed to continue their usual diet and to take two capsules of an assigned preparation three times daily with meals, either the aspartame or the placebo. The 1.8 g of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…On the other hand, the effects of chronic ingestion of aspartame in diabetics should be further studied. Stern et al (4) have already reported that in 43 NIDDM patients daily administration of 1.8 g of aspartame in capsules for 90 days did not affect the fasting plasma glucose level and had no prominent side effects , although they did not check the insulin level. Therefore, our present observations combined with the report of Stern et al (4), suggest that NIDDM patients can use aspartame as a food additive without affecting their blood glucose level .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effects of chronic ingestion of aspartame in diabetics should be further studied. Stern et al (4) have already reported that in 43 NIDDM patients daily administration of 1.8 g of aspartame in capsules for 90 days did not affect the fasting plasma glucose level and had no prominent side effects , although they did not check the insulin level. Therefore, our present observations combined with the report of Stern et al (4), suggest that NIDDM patients can use aspartame as a food additive without affecting their blood glucose level .…”
Section: Discussionmentioning
confidence: 99%
“…Of the few clinical studies involving diabetic subjects, observations have been limited to determination of the effects of aspartame loading on blood glucose, lipids, serum insulin, plasma glucagon, and glycosylated hemoglobin concentrations (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Few intervention studies have evaluated the effects of chronic LCS consumption on outcomes other than body weight [29, 48, 49, 66, 67]. Examples are clinical trials reporting on glycemia, in which no differences were observed following 6 weeks [49] or 90 days [66] treatment with aspartame compared to sucrose among adults with type 2 diabetes.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Examples are clinical trials reporting on glycemia, in which no differences were observed following 6 weeks [49] or 90 days [66] treatment with aspartame compared to sucrose among adults with type 2 diabetes. Similar findings were reported with saccharin [48] and rebaudioside A [46].…”
Section: Methodological Considerationsmentioning
confidence: 99%